Short-term clinical and radiological comparisons between two Medial Pivot Total Knee Arthroplasty implants with different geometries - Vecchini, Eugenio; Leandro, Ramazzini; Lunardelli, Enrico; Zancanaro, Fabio; Amarossi, Andrea; Anselmi, Angela; De Cristan, Damiano; Maluta, Tommaso; Magnan, Bruno; Ricci, Matteo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Different total knee arthroplasty (TKA) implants were created for the treatment of severe symptomatic gonarthrosis and Medial Pivot TKA (MP TKA) seem to reproduce the normal kinematics of the knee. We compare two different prosthetic designs of MP TKA in order to identify whether there is a difference between the two in terms of degree of patient satisfaction.  Methods: A total of 89 patients were analyzed. A group of 46 patients who benefited from a TKA with the Evolution® prosthesis and one of 43 patients who received a TKA with the Persona® prosthesis. KSS, OKS, FJS and the ROM were analyzed at follow up. Results: The values of KSS and OKS were similar between the two groups (p>0,05). Our statistical analysis revealed a statistically significant increase (p